2008
DOI: 10.1152/ajplung.90394.2008
|View full text |Cite
|
Sign up to set email alerts
|

LXR-induced reverse cholesterol transport in human airway smooth muscle is mediated exclusively by ABCA1

Abstract: The association of hypercholesterolemia and obesity with airway hyperresponsiveness has drawn increasing attention to the potential role of cholesterol and lipid homeostasis in lung physiology and in chronic pulmonary diseases such as asthma. We have recently shown that activation of the nuclear hormone receptor liver X receptor (LXR) stimulates cholesterol efflux in human airway smooth muscle (hASM) cells and induces expression of the ATP-binding cassette (ABC) transporters ABCA1 and ABCG1, members of a famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 48 publications
3
44
0
1
Order By: Relevance
“…As our data clearly show that the suppression of ABCG1 expression in both THP-1 and primary human macrophages, either transiently or by stable knockdown, is without effect on LXR-stimulated cholesterol efflux, then GSP2/LXR-dependent cholesterol efflux must be independent of ABCG1 expression and presumably linked to one of the plethora of other biological activities involving GPS2. In agreement with our observations, Delvecchio et al 18 recently reported that stimulation of cholesterol efflux to HDL by LXR agonists from human airway smooth muscle cells exclusively requires ABCA1 but not ABCG1. This result is in direct contrast with the situation in mouse macrophages, where deletion of ABCG1 significantly reduces cholesterol efflux from cells as we (this study and 2 ) and others have previously reported.…”
Section: Discussionsupporting
confidence: 94%
“…As our data clearly show that the suppression of ABCG1 expression in both THP-1 and primary human macrophages, either transiently or by stable knockdown, is without effect on LXR-stimulated cholesterol efflux, then GSP2/LXR-dependent cholesterol efflux must be independent of ABCG1 expression and presumably linked to one of the plethora of other biological activities involving GPS2. In agreement with our observations, Delvecchio et al 18 recently reported that stimulation of cholesterol efflux to HDL by LXR agonists from human airway smooth muscle cells exclusively requires ABCA1 but not ABCG1. This result is in direct contrast with the situation in mouse macrophages, where deletion of ABCG1 significantly reduces cholesterol efflux from cells as we (this study and 2 ) and others have previously reported.…”
Section: Discussionsupporting
confidence: 94%
“…Cholesterol efflux assays were performed as previously described with minor modifications (30). Briefly, SMCs from WT and FHL2-KO mice were seeded into 24-well-plate wells at a concentration of 3 ϫ 10 5 cells per ml and allowed to adhere overnight, followed by incubation for 24 h in DMEM-F-12 plus 20% FCS plus [ 3 H]cholesterol.…”
Section: Methodsmentioning
confidence: 99%
“…The LXR-regulated gene ABCA1 is a crucial mediator of cellular cholesterol efflux in SMCs (30,31). We therefore measured both ApoAI-and HDL-mediated cholesterol efflux in WT and FHL2-KO SMCs.…”
Section: Fhl2 Interacts With Lxr␣ and Lxr␤mentioning
confidence: 99%
“…In agreement with LXR's ability to inhibit the immune response in macrophage cells, Delvecchio et al [82,83] have recently shown that activation of LXR in airway smooth muscle cells can also inhibit chemokines and enhance cholesterol efflux from this cell type. These findings provide a potential pathway to target inflammatory airway diseases including asthma.…”
Section: Vi) Lung and Kidneymentioning
confidence: 73%